Cover Image. Issue 6 (17th October 2019) - Kong, Yong‐Ku; Lee, Jun‐Hyub; Lee, Ju‐Hee; Shin, Jae‐Min; Choi, Kyeong‐Hee
Abstract : Cover Caption : The cover image is based on the Full Article Perceived level of exertion compared to actual grip force exertion: The 50% phenomenon by Kyeong‐Hee Choi et al., https://doi.org/10.1002/hfm.20808 .